Happiness in the voice of university students (Research, Society and Development, 2021)
Objective: to understand the self-perception about happiness by university students in the nursing course. Methodology: this is an observational, cross-sectional study, with a qualitative approach, to understand the self-perception about happiness by university students of the nursing course in an institution in the Midwest of São Paulo. The sample was non-probabilistic for convenience, so it was defined by the presence at the time of data collection and acceptance to participate in the research. Data collection was carried out through a recorded interview, using a semi-structured questionnaire prepared by the authors. The data were analyzed using the methodological framework of Content Analysis. Results: 43 (30.2%) of the 142 (100%) students of the Nursing course participated in the higher education institution chosen for the same. Most are female (93.0%). According to the method, the data obtained in the interviews were grouped into two categories that contain subcategories: 1. Self-perceived happiness by undergraduate nursing students; 2. Self-perceived happiness and the dimensions that compose it. Final considerations: Happiness, a state considered positive, can significantly interfere favorably in attitudes, this feeling of satisfaction and transformation of emotions in valuing life, however, each individual has his way of expressing and relating, being a parameter of relationships family and social or also for some, an individualistic parameter, highlighting that all students were able to identify the reasons for their happiness or unhappiness.